The mediating effect of critical thinking between interest in learning and caring among nursing students: a cross-sectional study - Lai Kun Tong; Mio Leng Au; Yue Yi Li; Wai I. Ng; Si Chen Wang (BMC, 2023)
Abstract Background Previous studies have explored the influence of interest in learning on caring and critical thinking, as well as the relationship between caring and critical thinking. However, the mediating effect of critical thinking in interest learning and caring among nursing students has not been clarified. Methods Nursing students who enrolled for the 2021/2022 academic year in diploma, undergraduate, or graduate programs in five provinces of China (Guangdong, Sichuan, Jiangsu, Hunan and Macao). An online survey with a convenience sampling method was employed to collect data. The questionnaires were administered to 692 participants between January 20 and 26, 2022. Amos 26.0 was employed to establish the structural equation modelling and analyze the mediating effect of critical thinking on interest in learning and caring. Results The first regression equation showed that interest in learning significantly influenced caring (β = 0.339, p <  0.001). The third regression equation showed that critical thinking significantly influenced caring (β = 0.494, p <  0.001). The effect of interest in learning on caring was less in the third equation than in the first equation (β = 0.154 vs β = 0.339), which indicates partial mediation. Furthermore, interest in learning had an indirect positive effect (β = 0.186, p <  0.001) on caring mediated by critical thinking, with 95% confidence interval of 0.142 to 0.233. Conclusions Critical thinking was a significant mediator of the relationship between interest in learning and caring. It is suggested that nursing colleges and instructors should take into account students' interest in learning and critical thinking as potential intervention elements to enhance caring.